Oseanographic Conditions of Grenn Mussel Cultivation (Perna viridis) Using Multilevel Plastic Baskets Method in Salemo Island Waters, Pangkep Regency, Indonesia - Muhammad Farid Samawi; Abd. Rasyid Jalil; Shinta Werorilangi (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2023)
ABSTRACTCultivation of green mussels (Perna viridis) using multilevel plastic baskets has been carried out in the waters of Salemo Island, Pangkep Regency, Indonesia. The purpose of this study was to determine the oceanographic parameters that affect mussel cultivation at different water depths. The research treatment was placement on the surface and bottom of the waters (five meters deep) with different stocking densities. Green mussel cultivation is carried out for 4 months, namely May, June, July and August. Measurement of oceanographic parameters was carried out every month during green mussel cultivation, in situ, namely temperature, turbidity, salinity, pH, DO and those analyzed in the laboratory, namely TSS, TOM, Nitrate, Phosphate and the composition and abundance of plankton. Growth measurements of green mussels were also carried out, namely absolute weight and survival (SR). The results showed that the condition of oceanographic parameters differed between the surface and bottom waters, especially the parameters of TSS, turbidity, TOM, nutrients and plankton abundance. This situation is related to the absolute growth value and SR of mussels at different stocking densities and depths.Keywords: Oceanographic, green mussels, multilevel baskets, absolute growth, Salemo